2015
DOI: 10.17219/acem/38154
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Toxicity of Anticancer Chemotherapy in Patients with Colon Cancer

Abstract: Background. Modern anticancer chemotherapy can cause numerous adverse effects in the organism, whose functioning has already been disrupted by the neoplastic process itself. Objectives. The aim of the study was to evaluate and compare the frequency and severity of the toxicity of FOLFOX-4 and CLF-1 anticancer therapy in patients with colon cancer, and to analyze certain factors that might have increased the toxicity of the chemotherapy. Material and Methods. The study involved 64 patients suffering from genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 14 publications
1
20
1
1
Order By: Relevance
“…In the same study, weight per additional kilogram was associated with a slight decrease in risk of both acute and persistent neuropathy, which has been attributed to the fact that oxaliplatin is cleared in part via distribution into tissues . One study found increased risk among women, which was however not found in two other studies …”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…In the same study, weight per additional kilogram was associated with a slight decrease in risk of both acute and persistent neuropathy, which has been attributed to the fact that oxaliplatin is cleared in part via distribution into tissues . One study found increased risk among women, which was however not found in two other studies …”
Section: Resultsmentioning
confidence: 92%
“…An assessment of the quality of the 15 included studies was conducted based on criteria adapted from a previously published systematic review on oxaliplatin‐induced peripheral neuropathy and the STROBE Statement checklist (Table ). Only three studies were prospective, and the majority of studies failed to distinguish the acute and chronic forms of oxaliplatin‐induced peripheral neuropathy (Table ) . Seven studies investigated independent risk or prognostic factors by multivariate analyses .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the overall incidence of digestive cancer is higher in men [4042], the incidence of oxaliplatin-related non-pulmonary toxic symptoms (e.g., neurotoxicity) is higher in women [43], which thus leaves the question of a possible increase in male gender-related pulmonary toxicity unresolved.…”
Section: Resultsmentioning
confidence: 99%
“…Cabe destacar, a relevância dos episódios de diarreia graus 3/4, no qual, levam a sérias complicações como desidratação, íleo paralítico, hipocalemia, obstrução intestinal, acidose metabólica ou até mesmo toxicidade renal. 22 Além disso, na última década, diversos estudos têm revelado que o polimorfismo genético tem sido determinante na ocorrência das toxicidades gastrointestinais graves. [23][24][25][26] Nessa perspectiva, a identificação de biomarcadores, a associação de terapias alvo moleculares com os esquemas mFOLFOX6 e FOLFIRI, assim como variações/modificações desses esquemas, vêm sendo investigadas e sugeridas com o intuito de minimizar as reações gastrointestinais severas.…”
Section: Discussionunclassified